Improving Weight of Evidence Approaches to Chemical Evaluations. Issue 2 (16th December 2014) - Lutter, Randall; Abbott, Linda; Becker, Rick; Borgert, Chris; Bradley, Ann; Charnley, Gail; Dudley, Susan; Felsot, Alan; Golden, Nancy; Gray, George; Juberg, Daland; Mitchell, Mary; et al.
Abstract : Federal and other regulatory agencies often use or claim to use a weight of evidence (WoE) approach in chemical evaluation. Their approaches to the use of WoE, however, differ significantly, rely heavily on subjective professional judgment, and merit improvement. We review uses of WoE approaches in key articles in the peer‐reviewed scientific literature, and find significant variations. We find that a hypothesis‐based WoE approach, developed by Lorenz Rhomberg et al ., can provide a stronger scientific basis for chemical assessment while improving transparency and preserving the appropriate scope of professional judgment. Their approach, while still evolving, relies on the explicit specification of the hypothesized basis for using the information at hand to infer the ability of an agent to cause human health impacts or, more broadly, affect other endpoints of concern. We describe and endorse such a hypothesis‐based WoE approach to chemical evaluation.